Growth, content of sodium, chlorideand ion relation in castor bean under salt stress and nitrogen fertilization - Lima, Geovani Soares de; Nobre, Reginaldo Gomes; Gheyi, Hans Raj; Soares, Lauriane Almeida dos Anjos; Pinheiro, Francisco Wesley Alves; Dias, Adaan Sudário (Comunicata Scientiae, 2015)
The aim of this study was to evaluate the growth, the content of sodium, chloride and ion relation in castor bean cv. BRS Energia as a function of irrigation water salinity and nitrogen fertilization under field conditions in the TypicUsthorthent eutrophic soil of sandy loam texture in the municipality of Pombal, PB . The experimental design was randomized blocks, a 5x4 factorial, consisting of the combination of five levels of electrical conductivity of irrigation water - ECw (0.3, 1.2, 2.1, 3.0 and 3.9 dS m-1) and four doses of nitrogen-DN (70, 100, 130 and 160% of the recommended dose). The use of water with ECw above 0.3 dS m-1 negatively affected the plant height, stem diameter, number of leaves and leaf area; the content of sodium and chloride increased with the increase in ECwin all parts of the plant, and the content of chloride being higher than sodium; irrigation with water of ECw up to 3.7 dS m-1 resulted in an increase in the Na+/K+ in root tissues; the increase in application of DN affected positively the number of leaves,leaf area and chloride in leaf.